Move Man / Azam Hidayat Abdul Razak - Abdul Razak, Azam Hidayat (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Move Man is a Sport Perfume product by De'Xandra. De'xandra has been operating since 201 5. The company has been in operation for 6 years and produced many types of perfume products for example have perfume for man, women and car. The name 'Move Man' is symbolized to the man that involved in many sports activities such as, football, badminton and more. This is the limited edition product especially for the sport man. The main objective of this product is to make the product look different and special from other products and finally the product started to feel more refreshing for sports. In line with the tagline 'Until the End' the product keeps the body always smells fragrant even when sweating. The uniqueness of this product is available in three flavors which are deep energy, ice dive and pure game. The advantage of this product is the price is average with the other product out there. The concept design for the product is elegant, energetic and attractive for man. It also symbolize male superiority. Using bold & dark colors to make this product looks more power , gentle and elegant. Next, the packaging of product have a three different type of color such as red, blue and green . The three of these color also have the symbolic and meaning like red is represent for strength and energy and the blue is represent for cold and fresh. The green color also for calm and relaxing. For the product market, the competitors are not too much because there are not more competitors out there for man perfume especially for athlete and sport man. As we know, there are a lot of perfume for woman at market sale. In addition, for their price are also acceptable because this perfume is at high good of the quality and similar with the elite product in market. For my mission for this product is I want this product more excellent in market and useful for men and sport man. I also hope this perfume can be famous in Malaysia with high good rating and many people will know about this product soon. Lastly, my vision for this perfume is planning to expand this perfume get the good achievement in Asian.